KOMUNIKASI EFEKTIF ANTARA ORANGTUA DENGAN ANAK BERKEBUTUHAN KHUSUS TUNAGRAHITA DALAM MEMBIASAKAN BERIBADAH DI SLB NEGERI BREBES - Almardliyatul Wardatun Nisa A; M. Nurul Yamin; Muhammad Samsudin (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
Humans cannot be separated from daily communication in order to achieve effective interaction with others. Effective communication occurs when individuals understand and share common goals. Good communication between parents and children has a positive impact on family life; however, not all families experience effective communication, particularly families with children who have intellectual disabilities. This condition can hinder effective communication between parents and children. Therefore, this study aimed to describe effective communication between parents and children with mild intellectual disabilities at SLB Negeri Brebes, as well as to identify the supporting and inhibiting factors influencing such communication. This research employed a descriptive qualitative method. The subjects consisted of four families, each with parents who had children with mild intellectual disabilities. Data were collected primarily through interviews and supported by observations. The results showed that communication between parents and their children in all four families was effective, particularly in habituating worship activities, which was supported by the use of audiovisual media. Meanwhile, inhibiting factors of effective communication included children’s slow cognitive processing and emotional instability resulting from intellectual disabilities.